Engaging others, knowing ourselves : a Lutheran calling in a multi-religious world - LaHurd, Carol Joan Schersten; Lohre, Kathryn Mary; Jodock, Darrell, 1941- (Lutheran University Press, 2016)
Christians live and work in an increasingly multi-ethnic and multi-religious context. How does this affect their calling to serve their neighbors and their community? What resources does the Lutheran Christian tradition offer? Woven into this book are more than fifty stories of ELCA inter-religious engagement. These examples from local ministry settings are supplemented by practical tips, theological reflection, and historical analysis. The result is a guide for study, discussion, and action as a contribution toward the 500th observance of the Reformation in 2017and beyond--back cover.